2020
DOI: 10.3920/bm2020.0075
|View full text |Cite
|
Sign up to set email alerts
|

Lacticaseibacillus rhamnosus GG inhibits infection of human keratinocytes by Staphylococcus aureus through mechanisms involving cell surface molecules and pH reduction

Abstract: Beneficial bacteria represent an emerging tool against topical diseases, including infection caused by Staphylococcus aureus. Here, we investigated several anti-pathogenic mechanisms of the model probiotic Lacticaseibacillus rhamnosus GG against a clinical S. aureus isolate by implementing various mutants lacking important cell surface molecules. We analysed adhesion of L. rhamnosus and competitive adhesion with S. aureus to primary human keratinocytes, L. rhamnosus and S. aureus auto- and co-aggregation, S. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…For instance, in the model strain Lactocaseibacillus rhamnosus GG, SpaCBA pili have been described that mediate adhesion to intestinal mucus and epithelial cells (Kankainen et al, 2009). Recently, we also demonstrated that these pili are one of the key factors promoting its adhesion to human epithelial keratinocytes and interfering with adhesion of S. aureus (Spacova et al, 2020a(Spacova et al, ,2020b showing that the SpaCBA pili are adaptation factors in other body sites than the gut. For the URT, relatively good adherence of L. rhamnosus GG to the respiratory epithelial cell line Calu-3 and nasal epithelial cells of patients and healthy controls was observed ).…”
Section: Properties That Mediate the Activity Of Probiotics In The Urtmentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, in the model strain Lactocaseibacillus rhamnosus GG, SpaCBA pili have been described that mediate adhesion to intestinal mucus and epithelial cells (Kankainen et al, 2009). Recently, we also demonstrated that these pili are one of the key factors promoting its adhesion to human epithelial keratinocytes and interfering with adhesion of S. aureus (Spacova et al, 2020a(Spacova et al, ,2020b showing that the SpaCBA pili are adaptation factors in other body sites than the gut. For the URT, relatively good adherence of L. rhamnosus GG to the respiratory epithelial cell line Calu-3 and nasal epithelial cells of patients and healthy controls was observed ).…”
Section: Properties That Mediate the Activity Of Probiotics In The Urtmentioning
confidence: 85%
“…For CRS in particular, the EPOS2020 (European Position Paper on Rhinosinusitis and Nasal Polyps) steering group recently concluded, based on the small studies with limited sample sizes that are conducted up to now, that there is currently no evidence for the use of oral or topical URT probiotics as treatment option for CRS patients (Fokkens et al, 2020). It should be noted however that analysing probiotic interventions is highly challenging, and sweeping generalizations on their efficacy based on this limited amount of available studies is difficult, as also mentioned by the EPOS2020 steering group, considering the probiotic strain-specificity and multifactorial mechanisms of action that furthermore depend on the application site (Spacova et al, 2020a(Spacova et al, ,2020b. Such screenings for probiotic efficacy and safety demands a dedicated pipeline, where a combination of in silico, in vitro and in vivo models are advised.…”
Section: Substantiating the Efficacy Of Urt Probiotics In Vitro And In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Adhesins, particularly short ones like integral outer membrane proteins and autotransporters can be masked or shielded by exopolysaccharides (EPS), fimbriae and even secreted proteins [ 23 , 35–38 , 39 19]. In Lacticaseibacillus rhamnosus , EPS production masked adherence by spaCBA pili [ 38 ] and encapsulated Pasteurella multocida cells autoaggregated less than non-encapsulated (capsule-deficient) P. multocida [ 40 ]. Capsule interference could be due to its electrostatic negative charge [ 40 ] or sterical obstruction of autoaggregation factors [ 41 ].…”
Section: Modulation Of Autoaggregationmentioning
confidence: 99%
“…Probiotic organisms often protect against infection by autoaggregating or coaggregating with pathogens. Autoaggregation allows competitive exclusion and displacement of pathogens while coaggregation increases proximity of the co-aggregating probiotic bacteria's Type VI secretion systems and releases antimicrobial substance to the target pathogen [ 38 ]. The well-documented probiotic potential of Lacticaseibacillus rhamnosus GG lies in its immunogenic SpaCBA pili that mediate mucosal adherence and autoaggregation [ 70 ].…”
Section: Applications Of Autoaggregation Studiesmentioning
confidence: 99%